Variation of Blood Pressure Among Adults Residing in High and Low Salinity Areas - Sultana, Nadia; Hossain, Irin (Journal of Preventive and Social Medicine, 2025)
Background: Excessive salinity in drinking water poses ecological and health challenges, particularly increasing the risk of high blood pressure. Methods: A comparative cross-sectional study was conducted from January to December 2021 among 330 adults aged 18–49 years, selected using multistage sampling. High-salinity (Dacope, Khulna) and low-salinity (Singair, Manikganj) areas were studied. Data were collected through interviews with a pre-tested questionnaire, anthropometric and blood pressure measurements, and drinking water analysis. Results: Blood pressure measures were significantly higher in the high-salinity area compared to the low-salinity area. Mean systolic, diastolic, mean arterial, and pulse pressures in the high-salinity area were 126.784±0.666 mmHg, 83.200±0.737 mmHg, 97.744±0.642 mmHg, and 43.612±0.642 mmHg, respectively, while in the low-salinity area, they were 104.721±0.666 mmHg, 69.911±0.737 mmHg, 81.573±0.642 mmHg, and 34.974±0.642 mmHg. Adjusting for confounders such as age, family history of hypertension, extra salt intake, physical activity, and BMI, the differences remained significant, with systolic, diastolic, mean arterial, and pulse pressures higher by 22.064, 13.288, 16.171, and 8.637 mmHg, respectively, in high-salinity areas. Conclusion: Adults in high-salinity areas face greater risks of elevated blood pressure, likely to worsen with climate change and sea-level rise. These findings highlight the need for public health interventions, including awareness campaigns and policies, to mitigate health risks from salinity exposure in Bangladesh. JOPSOM 2024; 43(2): 38-43